THE STUDY OF SYNONYMY IN LINGUISTICS AND THE VIEWS OF SCIENTISTS ON ITS TYPES (Scientific journal of the Fergana State University, 2023)
The 20th century was a golden age for the field of synonymy. Famous linguists have created many works, adhering to a scientific approach to their views. As a result, data remained that can become a real school for linguists, researchers of our time. If in the created works the phenomenon of synonymy, synonymic relations, their types were written based on the requirements of that time, then at present they are one of the central issues in the field of semantics, and the definitions and classifications given by them have become more widespread than before. This article analyzes the views of world linguists on synonymy which is one of the semantic categories. Similarities and differences in the definitions and classifications are also given. It is considered that over the years, the scope of research has expanded, and the definitions of synonyms have become more refined.